El teatro cortesano en la Lima colonial: recepción y prácticas escénicas - Rodríguez Garrido, José A. (2008)
A significant group of Italian-style plays (i.e. stagings that made use of spectacular scenic resources) were performed in Lima in 1672-1747), always in connection with festivities of an imperial nature. Taking as its basis a corpus of fifteen theatrical works, this study examines the conditions of their reception as well as the material avenues that allowed for the development of this type of theater in the capital of the Peruvian viceroyalty. Topics of analysis include: the context and purpose of these representations, the place in which they were presented, their intended public, and the stage media they employed.